2013
DOI: 10.5296/jse.v3i4.4281
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of High School Dropout and Their Role in Dropout Prevention: An Initial Investigation

Abstract: Though students at-risk for school dropout appear to recognize the important contribution of teachers to students' persistence to graduation, it is unclear if teachers are equally aware of their empowering influence. Gaining a better understanding of teachers' beliefs about dropout is important to continued efforts to develop interventions that effectively support students to graduation. This article describes the results of a pilot study that surveyed 95 high school teachers from a Midwestern school district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, they can help teachers improve collaboration with students by explicitly seeking students’ input on their goals for their own education, as well as their thoughts on effective ways of achieving those goals. Research investigating teachers’ understanding of high school drop-out has found that while teachers report making an effort to connect with students is important, few teachers place the responsibility for student drop-out on themselves (e.g., Knesting-Lund et al, 2013). Using a working alliance framework, school psychologists can help educators to think differently about the critical role teacher-student relationships have regarding student success, and how to foster effective working relationships with students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they can help teachers improve collaboration with students by explicitly seeking students’ input on their goals for their own education, as well as their thoughts on effective ways of achieving those goals. Research investigating teachers’ understanding of high school drop-out has found that while teachers report making an effort to connect with students is important, few teachers place the responsibility for student drop-out on themselves (e.g., Knesting-Lund et al, 2013). Using a working alliance framework, school psychologists can help educators to think differently about the critical role teacher-student relationships have regarding student success, and how to foster effective working relationships with students.…”
Section: Discussionmentioning
confidence: 99%
“…First, a survey developed by Knesting-Lund et al (2013) was used to look at teachers' perceived role in high school dropout prevention. On this measure, participants answered five demographic questions (school, content area taught, grade level taught, years of teaching experience, gender) and four items looking at different variables related to school dropout.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests the importance of teachers believing in their effectiveness at helping their students persist in school, no matter what obstacles the students may be facing. However, some teachers may not see the positive influence they may have due to factors such as a belief that students' concerns are out of teachers' control (Knesting-Lund, Reese, & Boody, 2013). Yet, if teachers who work with at-risk students on a daily basis do not realize the importance of their interactions with students and the positive effect they can have on student educational outcomes, schools' prevention efforts may be less effective.…”
mentioning
confidence: 99%
“…It is interesting to compare the types of data we found relevant for instructors for early identification of non-thriving with the perceptions of end-users about the data relevant to prevent dropout. This may be inferred from the host of factors that teachers perceive as leading to dropout, including low academic achievement, lack of effort or motivation, irregular attendance, disciplinary issues, and lack of parental involvement (Doll, 2010;Kennedy, 2017;Knesting-Lund et al, 2013;Owen, 2009;Zabalou, 2021). In terms of data, the categories we found pertaining to non-thriving are similar to those associated with dropout, which strengthen the importance of the terminology shift we suggest here.…”
Section: Which Data Can Help In Predicting Non-thriving?mentioning
confidence: 99%